The pattern of change in Latin American banking: an overall view - TAMAGNA, F.M. (PSL Quarterly Review, 2014)
<!–[if gte mso 9]> 72 1024x768 <![endif]–> Amidst substantial political and economic change, the central banks of Latin America have outgrown their formative phase, reflecting in their development the pervasive effects of internal and external influence. Their contribution to the changing pattern of the economies has been reflected in the promotion of new ways and instruments of financing, the support of new types of financial institutions in public and private fields, and the assumption of intermediary roles between the government and the financial community at home, and between these and foreign and international institutions. The present work provides a general analysis of these developments in Latin American banking. The author first considers the impact of change on the financial structure before looking at the place and role of central banks. The development of monetary instruments and the framework of monetary policy are then analysed. Finally, the changing scope of the financial system is examined. JEL: G21, G28 <!–[if gte mso 9]> Normal 0 14 <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; –> <!–[endif] –>